Approaches to the creation of prophylactic - health-improving classes of women of the second mature age - Varvara Akulova (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to carry out the theoretical analysis and synthesis of experience of the organization of prophylactic - health-improving classes of women of the second mature age. Material & Methods: the complex of methods of the research was used in the course of carrying out the research at the theoretical level: analysis and synthesis, generalization, induction and deduction. Results: the information concerning approaches to the creation of prophylactic - health-improving classes of women of the second mature age is analyzed. The means of physical education, which are used in the course of classes with the specified contingent, are defined. Conclusions: the leading role of means of improving fitness at the organization of prophylactic - health-improving activity with the contingent of women of the second mature age is defined and the lack of approaches to planning of exercise stress depending on features of the spatial organization of body of women is established.